Behind every lie [large type] - McDonald, Christina (Thorndike Press large print core, 2020)
"If you can't remember it, how do you prove you didn't do it? Eva Hansen wakes in the hospital after being struck by lightning and discovers her mother, Kat, has been murdered. Eva was found unconscious down the street. She can't remember what happened but the police are highly suspicious of her. Determined to clear her name, Eva heads from Seattle to London--Kat's former home--for answers. But as she unravels her mother's carefully held secrets, Eva soon realizes that someone doesn't want her to know the truth. And with violent memories beginning to emerge, Eva doesn't know who to trust. Least of all herself."--